An application of microwaves refraction for inhomogeneous plasma diagnostic - Siusko, Y.V.; Kovtun, Yu.V. (Вопросы атомной науки и техники, 2021)
A brief review of the main microwave diagnostics methods of inhomogeneous plasma based on the refraction of microwaves is given. These methods make it possible to determine the plasma density distribution, the magnetic field distribution, the electron collision frequency, and the electron temperature profile. In addition, the determination of the average density of the peripheral plasma layers and the local inhomogeneities of the rotating plasma are also possible. The effect of refraction on the accuracy of determining the plasma parameters by using microwave methods for plasma diagnostics is considered. Наведено короткий огляд основних методів мікрохвильової діагностики неоднорідної плазми, що використовують рефракцію мікрохвиль. Ці методи дозволяють визначити розподіли густини плазми та магнітного поля, частоту зіткнень електронів і профіль електронної температури. Крім того, можливе визначення середньої густини периферійних шарів плазми та локальних неоднорідностей плазми, що обертається. Розглянуто вплив рефракції на точність визначення параметрів плазми при використанні мікрохвильових методів діагностики плазми. Приведен краткий обзор основных методов микроволновой диагностики неоднородной плазмы, использующих рефракцию микроволн. Эти методы позволяют определить распределения плотности плазмы и магнитного поля, частоту столкновений электронов и профиль электронной температуры. Кроме того, возможно определение средней плотности периферийных слоев плазмы и локальных неоднородностей вращающейся плазмы. Рассмотрено влияние рефракции на точность определения параметров плазмы при использовании микроволновых мeтодов диагностики плазмы.